Silencing of the FTO gene inhibits insulin secretion: An in vitro study using GRINCH cells. (5th September 2018) - Taneera, Jalal; Prasad, Rashmi B.; Dhaiban, Sarah; Mohammed, Abdul Khader; Haataja, Leena; Arvan, Peter; Hamad, Mawieh; Groop, Leif; Wollheim, Claes B.
Abstract: Expression of fat mass and obesity-associated gene ( FTO ) and ADP-ribosylation factor-like 15 ( ARL15 ) in human islets is inversely correlated with HbA1c . However, their impact on insulin secretion is still ambiguous. Here in, we investigated the role of FTO and ARL15 using GRINCH (Glucose-Responsive Insulin-secreting C-peptide-modified Human proinsulin) clonal rat β-cells. GRINCH cells have inserted GFP into the human C-peptide insulin gene. Hence, secreted CpepGFP served to monitor insulin secretion. mRNA silencing of FTO in GRINCH cells showed a significant reduction in glucose but not depolarization-stimulated insulin secretion, whereas ARL15 silencing had no effect. A significant down-regulation of insulin mRNA was observed in FTO knockdown cells. Type-2 Diabetic islets revealed a reduced expression of FTO mRNA. In conclusion, our data suggest that fluorescent CpepGFP released from GRINCH cells may serve as a convenient marker for insulin secretion. Silencing of FTO expression, but not ARL15, inhibits insulin secretion by affecting metabolic signaling. Highlights: GRINCH cells as a new tool to study pancreatic β-cell secretion facilitating drug screening. Knockdown of FTO expression inhibits glucose- but not potassium-stimulated insulin secretion. Knockdown of ARL15 expression has no impact on insulin secretion. FTO expression is lower in islets from T2D patients.